ANÁLISE DA EXPRESSÃO DO MIR-22 EM UMA LINHAGEM CELULAR DE CÂNCER DE BOCA - Santos, Orlando Ronaldy da Silva; Silva, Filipe de Albuquerque; Santos, Italo Alves; Melo, Guilhermie Duarte de; Abreu, Inayanne Praxedes de; Imai, Haruko; Almeida, Carlos Arthur Cardoso (Gep News, 2017)
Tipo de Apresentação: Comunicação Oral.